Labour Legends and Russian Gold : Bolshevism and the British Left Part 1 - Morgan, Kevin, 1961- (Bolshevism and the British left, 2014)
Investigating the relationship between various sects of the British Left and Bolshevism in the first half of the 20th century, this study provides insights into the history of political funding. With an examination of the attitudes towards Soviet Russia, broader questions about the character of the British Left between the 1890s and the 1940s are presented. From Lenin and the fierce internal conflicts and controversies in Communist Russia to George Lansbury and the rise of the Labour Party's newspaper, the Daily Herald, this resource provides compelling new arguments about the relationships between political parties and their funding.